Evaluation of Alcazar Scoring System to Differentiate Between Benign and Malignant Ovarian Masses- A Nepalese Perspective - Sharma, Rupesh; Shrestha, Deepak; Thapa, Krishna; Bhandari, Kiran (Journal of Lumbini Medical College, 2021)
Introduction: Ovarian cancer is the fifth most common cancer in Nepalese females and the tenth overall, accounting for 5% of the total new cases of cancer in females in 2020. Ultrasonography (USG) remains the primary tool for diagnosis and characterization of ovarian masses in which many grey-scale and Doppler characteristics are evaluated. Various scoring systems have been described incorporating different USG parameters to differentiate benign and malignant nature of the ovarian masses. Alcazar scoring system includes both grey-scale as well as Doppler characteristics of the ovarian masses and is one of the more widely used systems worldwide. Methods: This was an observational cross-sectional study based on 52 consecutive patients who were clinically suspected to have ovarian mass and referred for USG evaluation and who subsequently underwent surgery. Results: As confirmed by histopathology, 37 cases were benign and 15 were malignant masses. Alcazar system of scoring identified 34 out of 37 benign cases and 15 out of 15 malignant cases with sensitivity and specificity for diagnosing malignant cases of 83.3% and 91.1% respectively. Conclusion: Alcazar system of scoring is a highly effective tool to differentiate between benign and malignant ovarian masses and can be of great help in diagnosis, characterization and effective preoperative planning